Communicative Action and Post-Public Sphere Phenomenon - nurazizah firman (Palakka : Media and Islamic Communication, 2021)
Post public sphere is a conceptual term which derived from the author to describe the emergence of new public spaces called virtual or digital public spaces. The virtual public space appears together with advances of information technology, which not only transforms the communication space of society, but also disrupts communication patterns that take place in the real world into the virtual world. This is a digital era which marked by disruption in various fields of life, in social, cultural, and economic and political life. One of the symptoms that arise is the disruption of public space from the real world to the virtual or digital space. Virtual space becomes a medium where each individual communicates without being limited by space and time. The post-public sphere refers to the phenomenon of change (disruption) in the public space that has led demos to enter a new communication arena that is different and does not even relate to the old public space. The new communication arena operates in a virtual (digital) world that is radiated by social media such as Facebook, Instagram, WhatsApp, including the massive media currently being is the YouTube media. Thus, the presence of various kinds of social media also provides preference for communication spaces for individual citizens to access and disseminate information independently. In the sense of an individualized information on each subject of citizenship.